Factors Affecting Organizational Commitment of Employees in Healthcare Sector of Kathmandu Valley - Gurung, Jas Bahadur; Bastola, Nayana (Kanya Journal, 2022)
In today’s context the demand for healthcare service has increased due to people’s awareness on the importance of health and quality of life. Though there is a lot of advancement in medical technology employees are considered an important asset of an organization. Employees’ commitment is important matter to consider because the presence of committed employees helps in reducing absenteeism, delays and turnover in the organization. So, the aim of the study is to investigate the factors affecting organizational commitment of employees in healthcare sector of Kathmandu Valley. In order to fulfill the objectives of the study, the survey was conducted using a well-structured and self-administered questionnaire. The sample of 185 was randomly selected from sampling frame of 4683 employees of 11 private hospitals of Kathmandu Valley. Data were analyzed using descriptive statistics, correlation and regression analysis. The study revealed that the level of employee commitment is moderate in hospitals of Kathmandu Valley. The findings derived from multiple regression analysis confirmed that organizational reward and work-life balance are important factors that positive and significantly affect organizational commitment. It indicates that higher the organizational reward and work-life balance, higher would be the organizational commitment. However, supervisory support, training and development and organizational culture do have insignificant influence on organizational commitment of employees in health care sector of Kathmandu Valley. Thus, it is assured that the results from the study are more valid and they could have a significant policy implication for concerning health sector authorities of Nepal.